Study of the interactions between lactic acid-based deep eutectic solvents and bovine serum albumin. (25th January 2023) - Guo, Jingjing; Fu, Li; Wang, Qian; Peng, Yuling; Yuan, Yaoyao; Lin, Deyu; Sun, Yuehui; Wang, Hui; Guo, Tong
Abstract : The interactions between bovine serum albumin (BSA) and four lactic acid-based deep eutectic solvents (LADESs) were studied by spectroscopic and electrochemical methods under simulated physiological conditions. Abstract : The interactions between bovine serum albumin (BSA) and four lactic acid-based deep eutectic solvents (LADESs), namely lactic acid (LA): choline chloride (CC), LA: betaine, LA: polyethylene glycol (PEG), and LA: ZnCl2, were studied by spectroscopic and electrochemical methods under simulated physiological conditions. The binding constants, binding sites and quenching constants between the LADESs and BSA were calculated via measuring the fluorescence spectra and electrochemical curves at different temperatures, and the quenching type was determined to be static quenching. Through thermodynamic calculations and molecular docking, it was determined that the interaction forces between the LADESs and BSA are hydrogen bonds (H-bonds) and van der Waals (VdW) forces. According to Fōrster's theory, the energy transfer efficiency and the binding distance between the LADESs and BSA were calculated, and the quenching of fluorescence was attributed to the energy transfer. The binding rates of the BSA-LADES systems at different temperatures were calculated, and the ideal LADES extractant for BSA separation and purification was identified. Besides, the contents of the α-helix in BSA before and after its interaction with the LADESs were studied by circular dichroism (CD) spectroscopy.